Discriminant analysis of nitrogen treatments in switchgrass and high biomass sorghum using leaf and canopy-scale reflectance spectroscopy. Issue 10 (18th May 2016) - Foster, Anserd J.; Kakani, Vijaya Gopal; Ge, Jianjun; Gregory, Mark; Mosali, Jagadeesh
ABSTRACT: Recent advances in imaging, laboratory, and field spectroscopy (sometimes referred to as hyperspectral remote sensing) provide a unique opportunity to obtain critical information needed for understanding nitrogen (N) management in crop production systems. Therefore, the objective of this study was to identify wavelength regions and phenological timing useful for the prediction of N status from canopy and leaf spectra. Leaf and canopy spectral data were collected using an ASD FieldSpec FR spectroradiometer (350–2500 nm) at monthly intervals during 2011 and 2012. The crops evaluated in the study were switchgrass 'Alamo' ( Panicum virgatum L.) and high biomass sorghum 'Blade 5200' ( Sorghum bicolor ) grown to evaluate N applications rates on biomass yield and quality. The optimal wavelengths were determined based on principal component analysis (PCA) and the separation of the N treatments using stepwise discriminant analysis (SDA). The results showed similar canopy and leaf-scale reflectance for high biomass sorghum but not for switchgrass. The wavelengths found to be most important for separating the N treatments were 520–560, 650–690 nm (visible region), and 710–730 nm (red-edge region). Triangular greenness index (TGI) was the most useful index for discriminating the N application rates. The best time for differentiating the different N treatments was 4–6 weeks after planting or 2–4 weeks after N fertilization in high biomass sorghum and within 4 weeks after green-up in switchgrass. In general, the results indicate that spectroscopy is a viable tool that could be used to estimate the biochemical and biophysical characteristics in bioenergy crop production systems.